ChemInform Abstract: Interaction in the Molten System Rb2O‐P2O5‐TiO2‐NiO. Crystal Structure of the Langbeinite‐Related Rb2Ni0.5Ti1.5(PO4)3. Issue 39 (September 2015) - Strutynska, Nataliia Yu.; Bondarenko, Marina A.; Ogorodnyk, Ivan V.; Zatovsky, Igor V.; Slobodyanik, Nikolay S.; Baumer, Vyacheslav N.; Puzan, Anna N.
Abstract The formation of complex phosphates is investigated in melts containing Rb2CO3, H3PO4, TiO2, and NiO at different molar ratios of Rb:P = 0.5‐1.3, Ti:P = 0.15, Ti:Ni = 1.0 at 1073‐953 K (Pt crucible, 1273 K, 3 h).